(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The importance of information timing which is provided to parents while making decisions onchildcare, and that additional help for the searches regarding childcare could increase the stability andquality of decisions on childcare. Details on the options for childcare, comprising programme quality, isessential because parents might not know that such information exists or where to obtain it when theyhave to meet the demands of their employment quickly. Societal norms have a role in determining familypriorities decisions, and that these priorities are effective and emerge through interactions in thecontext. Making choices on early care as a family is a challenging task that requires harmonizing needswith what is accessible. In this paper families‟ understanding of ECE by following intervention has beeninvestigated.